2016
DOI: 10.1007/s11010-016-2687-0
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-12 inhibits the hepatocellular carcinoma growth by inducing macrophage polarization to the M1-like phenotype through downregulation of Stat-3

Abstract: Hepatocellular carcinoma is the third most common cause of cancer death worldwide. Novel early detection biomarkers and efficacious therapy strategies are needed. Macrophages recruited from circulation monocytes are the major component of solid cancer and play an important role in the carcinogenesis. Whether overexpression of L-12 in monocytes could induce the phenotype directional differentiation into tumoricidal M1 macrophages and inhibit HCC growth in tumor microenvironment was investigated in this study. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 39 publications
0
37
0
1
Order By: Relevance
“…IL12 is a heterodimer that is composed of two subunits, IL12α and IL12β with the active form of IL12 p70 . It has also been confirmed to inhibit tumor growth by inducing macrophages polarization to M1‐ like phenotype in hepatocellular carcinoma . We further carried out investigations to explore the role of PKCα in the production of cytokines in human colon cancer cells.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…IL12 is a heterodimer that is composed of two subunits, IL12α and IL12β with the active form of IL12 p70 . It has also been confirmed to inhibit tumor growth by inducing macrophages polarization to M1‐ like phenotype in hepatocellular carcinoma . We further carried out investigations to explore the role of PKCα in the production of cytokines in human colon cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…34 It has also been confirmed to inhibit tumor growth by inducing macrophages polarization to M1-like phenotype in hepatocellular carcinoma. 12 We further carried out investigations to explore the role of PKCα in the production of cytokines in human colon cancer cells. In our study, elevated IL12B and CSF2 gene expression was observed in PKCα-overexpressed colon cancer cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, depleting Tregs and promoting T effector cell activity may be a potential therapeutic target (39). Moreover, IL-12 has been shown to suppress Treg cell activity and has demonstrated promising antitumor responses in mouse models (40)(41)(42).…”
Section: Immune Cellsmentioning
confidence: 99%